Tjukurpa nyakula wangkanytjaku 2 = Story to read 2 - Armstrong, Kanytjupayi; Eckert, Ann.; Broad, Marian; Pitjantjatjara Bible Translation Project ([Alice Springs, N.T.] : Pitjantjatjara Bible Translation Project, 1998)
Primer.
Includes English translation on leaf 7.
Keywords: Pitjantjatjara language -- Readers; Pitjantjatjara people (C6) (NT SG52-11); Pitjantjatjara language (C6) (NT SG52-11); Education - Language - Indigenous languages - Readers and primers; Northern Territory - Central NT